A Comprehensive Study of Online Internet Buyers Trust, Trustworthiness and Purchasing behavior in Indian Perspective (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Electronic commerce does not only give the consumer a broader selection of business and items but it also gives information concerned companies, various products and also competitors. These consumers can then compare these to each other and find the best deals. Good quality web sites also offer useful information to the consumer. A salesperson in a store would not necessarily have access to these kinds of lists so the information he would give would only be facts about different products instead of real customers reviews. Consumers often can interact with the merchants site to create exactly .The web really enables the whole business process to be much more efficient and the consumers will get exactly what they want. This study aims to fill this void by exploring the attributes of trust, trustworthiness and purchasing behavior can be developed in online transaction. The anticipated research results thus seize the probable to make a significant role to the internet based marketing and customer overall satisfaction.